The strategy of Marketable Public Relations Internationally Analytical study of the websites of “ Apple “ and “Samsung “ on the internet: (A research drawn from a Master Degree thesis) - Yassen, Aya Hamza; Al-azawey, Salem Jassim (ALBAHITH ALALAMI, 2020)
The international organizations showed their interest in the marketable public relations, with their activities, means and strategies, they play a crucial role in marketing products, services and ideas of the institution. They are considered to be the link between the company and its public, They are responsible for presenting the institution to the public, with honest transmission of the information. This gives a good impression to the institution, in a way the institution and its products become consistent with the needs and interests of the public.  Based on this, the research aims to identify the strategies used by the marketable public relations internationally.  The researcher used the survey method which consists of collecting data about the phenomenon, organizing it, and then analyzing it to end up with indicators and results of the study. The researcher also analyzed the contents in order to identify the strategies used in Apple and Samsung websites. She concluded that both Samsung and Apple succeeded in using  the marketable public relations on their websites in a planned and organized way. Samsung and Apple also relied primarily on emotion, then, on logic in their posts in order to persuade the public.